High‐Voltage Supercapacitors Based on Aqueous Electrolytes. Issue 4 (15th November 2018) - Zang, Xining; Shen, Caiwei; Sanghadasa, Mohan; Lin, Liwei
Abstract: Supercapacitors with high power density and life cycles are an important family of power supplies among energy storage systems. The operating voltage window of a supercapacitor is determined by both the chemistry of electrode materials and the electrochemical kinetics of electrolytes while the water hydrolysis potential of 1.23 V is the typical limit for capacitors based on aqueous electrolytes. Here, we briefly outline the working mechanism of electrochemical supercapacitors, including electron double layer capacitors (EDLC) and pseudo‐capacitors, and investigate the limitations of their working voltages. The principles and examples of different designs of electrodes and electrolytes for high‐voltage supercapacitors beyond the hydrolysis limit are discussed, such as asymmetric electrodes, high concentration electrolytes, and electrolytes with different pH values. Insights into high voltage capacitor cells and future prospects are provided for the development of electrochemical energy storage systems. Abstract : Bring on the water ! In this review, key elements that decide the operation voltage of electrochemical supercapacitor are discussed. Electrolyte and electrode design are summarized for high voltage supercapacitors in aqueous system.